2011
DOI: 10.1177/0310057x1103900110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Ondansetron on Sensory and Motor Block after Spinal Anaesthesia with Hyperbaric Bupivacaine

Abstract: Ondansetron is a potent antiemetic and a competitive antagonist at serotonin receptors, which are also involved in modulation of pain. This study was designed to assess the effect of systemic ondansetron on sensory and motor block after subarachnoid anaesthesia with hyperbaric bupivacaine. Sixty patients undergoing transurethral resection of bladder tumours were randomly assigned to one of two groups. Group 1 received 2 ml (4 mg) of ondansetron whereas patients in group 2 received 2 ml of normal saline 15 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Our study also confirms the finding that ondansetron does not affect the density of both sensory and motor blocks after subarachnoid anesthesia. 23 Our results suggest that ondansetron 8 mg is not effective in attenuating hypotension after subarachnoid anesthesia. However, there are limitations to our study.…”
Section: Discussionmentioning
confidence: 61%
“…Our study also confirms the finding that ondansetron does not affect the density of both sensory and motor blocks after subarachnoid anesthesia. 23 Our results suggest that ondansetron 8 mg is not effective in attenuating hypotension after subarachnoid anesthesia. However, there are limitations to our study.…”
Section: Discussionmentioning
confidence: 61%
“…Similar results have also been seen with ondansetron administered to patient prior to spinal anesthesia. [81516]…”
Section: Discussionmentioning
confidence: 99%
“…Similar lack of effects on motor blockade has also been seen in other studies using other 5-HT3 receptors antagonists. [789151619]…”
Section: Discussionmentioning
confidence: 99%
“…In one study, ondansetron administered to prevent nausea and vomiting interrupted sensory deprivation in spinal anesthesia performed with lidocain [2]. Another study showed that other 5-HT3 antagonists such as granisetron enhanced recovery of the sensory nerves during spinal anesthesia [3]. Palonosetron, a second-generation 5-HT3 receptor antagonist approved in 2003, is known to have the strongest affinity to the 5-HT3 receptor, with a receptor binding affinity about 30 times stronger than that of ondansetron and granisetron.…”
mentioning
confidence: 99%